The Influence of Entrepreneurship Education and Digital Literacy in Forming Entrepreneurial Competence - Chandra, Jony; Hendayana, Yayan (Dinasti International Journal of Management Science, 2024)
This research was conducted to determine the influence of Entrepreneurship Education (Entrepreneurship Education) on entrepreneurial competence. To determine the influence of digital literacy on entrepreneurial competence. The method used in this research is a literature review or literature study. Namely by collecting various relevant information related to the variables discussed. Through various sources and electronic media, the author will then articulate arguments based on existing theories and previous research. The findings in this research state that Entrepreneurship Education and Digital Literacy have a positive and significant effect on Forming Entrepreneurial Competence. Entrepreneurship education and digital literacy have a very important role in forming entrepreneurial competencies in individuals.